2020
DOI: 10.3390/fib8040024
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Electrospun Polyaniline/Polyvinylpyrrolidone Nanofibers: Electrical and Morphological Characterization of New Yarns for Electronic Textiles

Abstract: Advanced functionalities textiles embedding electronic fibers, yarns and fabrics are a demand for innovative smart cloths. Conductive electrospun membranes and yarns based on polyaniline/polyvinylpyrrolidone (PANI/PVP) were investigated using the chemical modification of PANI instead of using conventional coating processes as in-situ polymerization. PANI was synthesized from the aniline monomer and the influence of the oxidant-to-monomer ratio on electrical conductivity was studied. The optimized conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Conductivity is almost constant up to 3Hz beyond which it gradually increases, and, finally, after 4 Hz, conductivity jumps exponentially, which is also the characteristic peak of disordered semiconductor materials. It is observed that the polyaniline fiber has a higher conductivity of 1.23 S/cm compared to the bulk polyaniline [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conductivity is almost constant up to 3Hz beyond which it gradually increases, and, finally, after 4 Hz, conductivity jumps exponentially, which is also the characteristic peak of disordered semiconductor materials. It is observed that the polyaniline fiber has a higher conductivity of 1.23 S/cm compared to the bulk polyaniline [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides PEDOT:PSS, other conductive polymers can be used to prepare conductive coatings or intrinsically conductive fibers. Typical other materials are polyaniline (PAni) [34,35] and polypyrrole (PPy) [36].…”
Section: Conductive Yarns and Fabricsmentioning
confidence: 99%
“…4 Polymer electrospun fibers have unique properties due to their high surface-to-volume ratio, fiber-length-todiameter aspect ratio, 5 and porosity (generally ≥70%). 6 Nanofibers can be used for diverse applications such as filtration, 7 electronic textiles, 8,9 drug delivery, 5 tissue engineering, [10][11][12] wound dressing, 13 sensors, 14,15 and composites. 16 The electrospinning process stimulates the electrified liquid jets to whip and elongate to form fine fibers.…”
Section: Introductionmentioning
confidence: 99%
“…49 Doped PANI usage in polymer blend solutions has been reported extensively in the literature. 8,14,21,26,35,37,42,46,[50][51][52][53] Much of the current literature presents varying results on the electrospun materials' enhanced electrical conductivity based on the doped PANI. There are several disadvantages associated with the use of doped PANI as compared to using pure PANI.…”
Section: Introductionmentioning
confidence: 99%